Pengaruh penerapan skema work from anywhere (WFA) di direktorat komunikasi dan bimbingan pengguna jasa - Faizur, Muhamad; Khoiriani, Annida; Susianti, Susianti (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2023)
The Covid-19 pandemic has brought various changes in various aspects of life and activities, one of which is in the work scheme. Policies that have so far prioritized physical implementation, demand changes to remote work schemes. The government implements the PSBB (Large-Scale Social Restrictions) policy as stipulated in Permenkes No. 9 of 2020 concerning Guidelines for Large-Scale Social Restrictions as a guideline for preventing the transmission of diseases caused by the widespread Covid-19 virus. Some activities are directed at home except defense, security, health services and several vital sectors. The new normal is a change in behavior to continue carrying out normal activities but with the addition of implementing health protocols to prevent transmission of Covid-19. This new order adapts all activities by cultivating hygiene and health disciplines. New normal is implemented in all lines including government activities in public services, for example, the e-government program for the State Civil Apparatus in the new normal order. In this order, there are several new programs implemented, such as working at home (WFH), working in an office (WFO), to working from anywhere (WFA). This study aims to determine the effectiveness of implementing the Work from Anywhere scheme as well as to provide suggestions and recommendations on various weaknesses found in WFA scheme procedures based on employee satisfaction.